THE INFLUENCE OF LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE PT. ASSA RENT - Indra Setiawan (Kusuma Negara Business School, 2019)
To achieve this goal, every organization needs human resources. Human resources and leadership need to be well integrated because these two things can mutually influence employee performance. Good employee performance can achieve the desired organizational or company goals. This is a challenge for the company to produce the best employee performance. In this study, the formulation of the problem that will be assessed is whether there is an influence between the autocratic leadership style and work motivation on employee performance, whether there is an influence between work motivation on employee performance, is there an influence between leadership style and motivation on employee performance at PT Assa Rent on year 2019. This research is a qualitative study, with data collection techniques, interview techniques, observation, literature study, and questionnaires (questionnaire). From this research, the conclusion that the writer can take is that when the leadership style and work motivation are tested jointly, there is a significant influence between the leadership style and work motivation on employee performance at PT Assa Rent. If seen from its dominance, the variable of work motivation is more dominantly affecting employee performance compared to the leadership style variable.